(untitled) (Південний архів (історичні науки), 2021)
The purpose of the work. The article is about the personality of a OUN(r) March Groups member Yulian Wojtowych and his work in the field of education in Kherson during the German occupation in particular. The attention is focused on the history of foundingan agricultural school where Yulian Wojtowych taught history and geography. The historiography of the issue embraces works which cover the topic of OUN activities at the South of Ukraine, particularly that of Lev Shankovsky and Yevgen Gorburov, and Mykola Shytiuk. OUN March Groups members’ memoirs and Soviet State Security agencies’investigatoryfiles, as well as operative ones, about OUN activities in Kherson became sources for this research. Results and scientific novelty of the research. It was found out, that educational line was one of the primary ones in the OUN activity in Kherson during the German occupation. Ukrainian nationalists paid special attention to teaching the history of Ukraine in the learning process because this very subject together with geography formed the students’ outlook. As OUN members believed, it was the school which shaped future architects of the Ukrainian State. Yulian Wojtowych who had had complete theological education was actually a teacher of history and geography, participated in composing the history of Ukraine curricula for Kherson schools. In thecrisis situation in education sphere caused by the policy of the Nazi occupational authorities, special (professional) educational institutions, namely agricultural school, were for OUN members of particular interest. The occupational authorities had their own interest in opening such schools which would train mid-level professionals (“help staff”). OUN members considered them as opportunities for Ukrainian youth to obtain education and for themselves to recruit new staff for the struggle for independence of Ukraine. Due to his nationalist underground activities and realization of the organisation leaders’ instructions on the Ukrainian education development, Yulian Wojtowych suffered repressions from the Nazi secret services and had to undergothe “Vodokachka” camp, Buchenwald, Dora and Bergen-Belsen.